THE PRACTICE OF APPLYING LEAN EDUCATION IN HIGHER EDUCATION INSTITUTIONS - Valieva Nasiba Khadiyatullayevna (CANADA - SCIENTIFIC REVIEW OF THE PROBLEMS AND PROSPECTS OF MODERN SCIENCE AND EDUCATION, 2025)
The paper presents options for using lean teaching methods in the practice of higher education institutions in the digital economy. Taking into account the transition from traditional to electronic education, the main directions for realizing the possibilities of lean methodology are highlighted.